Potassium-Competitive Acid Blockers versus Proton Pump Inhibitors for Healing of Erosive Esophagitis: A Systematic Review and Meta-Analysis - Gede Made Cahya Trisna Pratama; Komang Agus Wira Nugraha (PT BMW Journal Sejahtera, 2026)
Background: Erosive esophagitis (EE) is a prevalent manifestation of gastroesophageal reflux disease that requires potent acid suppression for mucosal recovery. While proton pump inhibitors (PPIs) are the standard therapy, their efficacy is often limited by slow onset and genetic polymorphisms. Potassium-competitive acid blockers (P-CABs) have emerged as a novel alternative with superior pharmacokinetic properties. Objective: This systematic review and meta-analysis aimed to evaluate the comparative efficacy and safety of P-CABs versus PPIs in achieving mucosal healing and symptom relief in patients with EE. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted across major databases for randomized controlled trials (RCTs) published through 2025. Nine RCTs involving 2,927 participants were included. Data on healing rates at weeks 4 and 8, heartburn disappearance, serum gastrin levels, and adverse events were synthesized using fixed and random-effects models. Results: P-CABs demonstrated significant superiority in mucosal healing compared to PPIs at week 4 (OR: 1.47; 95% CI: 1.09–2.00; p=0.01) and week 8 (OR: 2.04; 95% CI: 1.41–2.95; p=0.0002). P-CABs also achieved faster heartburn disappearance (MD: -1.29 days; p=0.01). Although P-CABs resulted in higher serum gastrin levels (MD: 121.74 pg/mL; p=0.0007), safety profiles were comparable between groups with no significant differences in adverse events. Conclusion: P-CABs provide faster and more effective mucosal healing than PPIs with a comparable safety profile, representing a robust breakthrough for the management of erosive esophagitis.